Panorama Strategy toward Students’ Reading Comprehension Skill: An Experimental Study - Fitriani, Ika (English Education Study Program, 2024)
This current quasi experimental research tried to investigate the main effect of PANORAMA reading strategy which consists of Previewing, Annotating, Noting Vocabulary, Organizing, Reading aloud, Assessing, Monitoring, Answering, compared to the combined translation and reading aloud (TRA) toward students’ reading comprehension. After the process of treatment, the results of the two groups were compared and analyzed statistically. It was revealed that the difference between the control and the experimental groups was not significant. Despite the insignificant difference, PANORAMA is potential to be considered as an alternative of reading strategy to help students to comprehend English reading passage.